Informational Ergonomics: A Study on How Symbols are Used in Graphic Marks - Silva, J. C R P [UNESP]; Paschoarelli, L. C. [UNESP]; Silva, J. C P [UNESP]; Friso, V. R. [UNESP] (Elsevier, 2015)
Mankind uses symbols to communicate since prehistoric times. Over time these symbols become more complex and contain a denser message. The apex of contemporary times is the brands that use institutional symbol or graphic language to get their message across. The lack of concern about how this is being applied has caused visual discomfort, which is called visual noise. Ergonomics informational enables a division of the aspects that add the message symbol, facilitating a deeper analysis of the quality of the message to which you want to pass to the user of this brand. Thus providing the methods for professionals confirm that the message contained in the symbol is high quality.
Keywords: Brands; Graphic design; Informational ergonomics; Symbols